PENDEKATAN KOMUNIKASI SECARA MAUIZATUL HASANAH - Junaidi Junaidi (Ar-Raniry State Islamic University, Indonesia, 2020)
Many of Islamic concepts are not implemented in daily life. This is due to the way the delivery of religious messages is still not quite right, God says Q. An-Nahl, 125.